Comparative Activities of Clinafloxacin, Grepafloxacin, Levofloxacin, Moxifloxacin, Ofloxacin, Sparfloxacin, and Trovafloxacin and Nonquinolones Linozelid, Quinupristin-Dalfopristin, Gentamicin, and Vancomycin against Clinical Isolates of Ciprofloxacin-Resistant and -Susceptible Staphylococcus aureus Strains - Jones, Mark E. (American Society for Microbiology, 1999)
The activities of eight fluoroquinolones and linezolid, quinupristin-dalfopristin (Synercid), gentamicin, and vancomycin were tested against 96 ciprofloxacin-susceptible and 205 ciprofloxacin-resistant Staphylococcus aureus strains. Overall, clinafloxacin, followed by moxifloxacin and trovafloxacin, was the most active quinolone tested. For all isolates, linezolid and quinupristin-dalfopristin showed activities that were at least comparable to vancomycin, with no cross-resistance to any other test compound.